The analysis of elements geometry position in the Iranian garden structure - Mohammadi, Hanieh; Valibeig, Nima (Journal of Architecture and Urbanism, 2018)
Iranian garden has been known as a specific architecture in the whole world. Among all its special features, the geometrical structure of Iranian garden has always attracted the attention of architects and researchers. Nowadays, despite numerous studies on the Iranian gardens, the lack of geometrical studies and the extension of some old concepts have led to recognize the Iranian gardens based on a unique pattern in terms of geometry. This pattern has been known as an archetype and typifies the Iranian Garden Geometry as a quarter pattern. That it could not be a true hypothesis, because the impact of garden components on its structure has been neglected. Investigating geometric position of garden elements and their relationship with the general form of garden would provide more accurate theoretical basis for Iranian garden design. In addition, this approach could help experts to retrieve the ruined part of historical gardens. So far, extensive garden studies have been carried out more on the symbolic concepts, components introduction and typology according to times and locations. This article is the first attempt to study each common element’s geometry to realize how the spatial structures could be effective in the garden formation. This paper aims to recognize the architectural geometric logic of gardens based on library studies and field recordings.